2017
DOI: 10.1039/c7qo00084g
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed direct borylation of alkyl, alkenyl and aryl halides with B(dan)

Abstract: Copper-catalyzed reaction of organic halides with an unsymmetrical diboron, (pin)B–B(dan), which leads to the direct formation of masked organoboron compounds, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Since then further developments of this copper variant of the classical palladium catalysed Miyaura boryation have included borylations in shorter reaction times using designer bicyclic NHC ligands, 128 the use of alternative diboron reagents (e.g. Bin-Bdan) leading to aryl-Bdan esters, 129 co-catalyst combinations that give even greater functional group tolerance enabling phenols, amides, esters and ketones to be used in reactions undertaken open to the air (Scheme 30iii), 130 and applications to other nucleofuges, including arylfluorides, although this last transformation probably proceeds by an S RN 1 pathway (Scheme 30iv). 131,132 In a similar fashion, alkyl (sp 3 ) halides can undergo coppermediated borylation.…”
Section: Copper Catalysed C-x Borylationmentioning
confidence: 99%
“…Since then further developments of this copper variant of the classical palladium catalysed Miyaura boryation have included borylations in shorter reaction times using designer bicyclic NHC ligands, 128 the use of alternative diboron reagents (e.g. Bin-Bdan) leading to aryl-Bdan esters, 129 co-catalyst combinations that give even greater functional group tolerance enabling phenols, amides, esters and ketones to be used in reactions undertaken open to the air (Scheme 30iii), 130 and applications to other nucleofuges, including arylfluorides, although this last transformation probably proceeds by an S RN 1 pathway (Scheme 30iv). 131,132 In a similar fashion, alkyl (sp 3 ) halides can undergo coppermediated borylation.…”
Section: Copper Catalysed C-x Borylationmentioning
confidence: 99%
“…In 2017, Yoshida found that copper‐catalyzed borylative substitution of organic halides with (pin)B−B(dan) smoothly took place to give a variety of alkyl, alkenyl, aryl and heteroaryl–B(dan)s in a straightforward manner (Scheme 37). [33] Especially, it is worth noting that 2‐pyridyl–B(dan) obtained by this reaction showed excellent stability toward aqueous work‐up and isolation by Florisil column chromatography, which is in marked contrast to the well‐known instability of its B(OH) 2 ‐ and B(pin)‐counterparts.…”
Section: B(dan)‐installing Reactionsmentioning
confidence: 93%
“…Since our report on the copper‐catalyzed Markovnikov hydroboration of terminal alkynes, a borylcopper species [Cu−B(dan)] has been the linchpin of the catalytic B(dan)‐installing reactions ,. In addition to the well‐established addition reactions across unsaturated carbon−carbon bonds such as borylstannylation, carboboration, aminoboration and conjugate addition, borylative substitution of organic halides, also occurs smoothly, demonstrating that Cu−B(dan) can act as a boron nucleophile. Although various R−B(dan) (R=alkyl, alkenyl, aryl and allyl) are directly accessible by the substitution, a representative problem awaiting solution is low α/γ‐selectivity in the allylic borylation of allylic halides (Scheme ), which should result from a radical pathway operative therein.…”
Section: Methodsmentioning
confidence: 99%